Evaluation of the Restructuring Process by Nurses in Nursing Services Management: A Qualitative Study - Bilgen Özlük; Ülkü Baykal (Association of Nurse Managers, 2020)
INTRODUCTION: A successful restructuring process in order to increase the quality and effectiveness of nursing services contributes to organizational development by positively affecting organizational processes and outcomes. The aim of this study was to determine how nurses were restructuring in nursing services management. METHODS: This study, designed in a qualitative design, is based on a prospective phenomenological approach to define a three-year process.. A total of 30 interviews were conducted with 17 nurses working in a private hospital and selected for maximum diversity sampling. In the data collection process, semi-structured interview form consisting of open-ended questions and a voice recorder were used by individual interview method. The data were analyzed by descriptive analysis. RESULTS: The findings of the study were examined by forming three main themes and thirteen sub-themes: organizational structure and operation, working conditions and reasons for thinking about leaving work. DISCUSSION AND CONCLUSION: During the restructuring process, it was seen that nurses were not satisfied due to reasons such as appointment of non-nurses by profession, negative working conditions, excess workload and insufficient wage. In organizations that successfully manage this process, it is recommended that professional competence and corporate merit be at the desired level, and that employee satisfaction and organizational development should be given importance.